Inheriting Versus Developing Data Analytic Tests and Auditors’ Professional Skepticism - LI, XIAOXING; BRAZEL, JOSEPH F.; GOLD, ANNA; LEIBY, JUSTIN (Journal of Accounting Research, 2026)
ABSTRACT As the use of audit data analytic tests (ADA) becomes increasingly established in practice, auditors will often confront situations in which they inherit ADA developed by others, as opposed to developing the ADA themselves. Despite the potential benefits of ADA, inheriting ADA could decrease auditors’ skeptical actions by diminishing their psychological ownership of the ADA. In an experiment where an ADA identifies a fraud red flag, we find that auditors who inherited the ADA are less likely to exercise skeptical actions than those who were personally involved in its development. We then provide evidence that informing auditors who inherit an ADA about the test development activities (e.g., a brief memorandum documenting the ADA's development) mitigates the negative effect of inheriting the ADA. Evidence from mediation analyses suggests that these effects are driven by decreased psychological ownership when auditors inherit the ADA.